2018
DOI: 10.1016/j.jtcvs.2017.11.089
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of a simple and effective approach to aortic root and arch repair in acute type A aortic dissection

Abstract: Direct aortic root and arch repair with approximation of the aortic wall without use of technical adjuncts is safe and effective for patients with ATAAD. If warranted, preservation of the native aortic valve should be considered for a potential survival benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 18 publications
2
59
0
Order By: Relevance
“…Besides, persistent blood flow in the aortic root false lumen after surgical repair can compress coronary artery origins, which may cause myocardial ischemia. 12) Therefore, aortic root reinforcement is critical in ATAAD treatment, and despite efforts to reduce complications, aortic root management remains a challenge for cardiac sur-NEW TECHNIQUE FOR AORTIC ROOT REINFORCEMENT geons.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, persistent blood flow in the aortic root false lumen after surgical repair can compress coronary artery origins, which may cause myocardial ischemia. 12) Therefore, aortic root reinforcement is critical in ATAAD treatment, and despite efforts to reduce complications, aortic root management remains a challenge for cardiac sur-NEW TECHNIQUE FOR AORTIC ROOT REINFORCEMENT geons.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al 5 reported a set of contrasting results from their single center study, compared to various other articles as seen in Table A1.…”
Section: Replacing the Root A Burden On Mid To Long Term Outcomes?mentioning
confidence: 99%
“…Surgical intervention on the aortic root remains controversial and debatable. [4][5][6][7] Acute aortic dissection repair can necessitate a variety of operations, from simple replacement of the ascending aorta to aortic root replacement or a version of total arch replacement. There are differing opinions regarding what constitutes the "appropriate" repair of the acutely dissected aorta, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] a tear tailored approach is a trend that we normally follow; however, this is not generalizable across many different centers.…”
mentioning
confidence: 99%
“…Root replacement was performed as a total root (BioBentall with Freestyle ) (n=7), inclusion root with a Freestyle bioprosthesis (n=4), or David valve-sparing aortic root replacement (n=2); all of which are current practice in our group. If criteria were not met for aortic root replacement, aortic root repair was performed (n=52) by preserving the aortic valve and all sinuses of Valsalva based on surgeons' preference as previously described (20)(21)(22). With aortic valve pathology in the absence of aortic root pathology, an isolated aortic valve replacement was performed (n=1).…”
Section: Surgical Techniquesmentioning
confidence: 99%